Kerawanan Anak: Antara Realitas Sosial dan Spirit Islam - Firdaus Dahlan; Kasiim Salenda; Rahmatiah HL; Ria Renita Abbas (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Child survival in Indonesia is in a lagging position and has not yet touched upon the social conditions of children, including health factors such as affordability of health services, economic factors and educational factors, all of which greatly determine the condition of children's survival and even increase the high mortality rate (child deaths). The position of Child Survival as an urgency for the quality of resources for the next generation, encourages this research to explore several things related to the social conditions of Indonesian children who are covered by child vulnerability. Children who experience social vulnerability are very vulnerable to experiencing negative conditions and can even experience death in the child's time. This research states that children's vulnerability occurs because they are not yet in a position as a social investment and are often ignored by the state for two reasons: first, the parameters for successful development in the social sector have not been maximized and second, issues regarding children are considered only domestic matters which are addressed after more macro issues such as poverty can be minimized. If it is related to Islamic teachings, children have a main and special position in the Koran and Hadith texts which encourage treating a child humanely, receiving education and teaching noble moral skills so that in the future they will be responsible in facing a future full of challenges.